2019
DOI: 10.5018/economics-ejournal.ja.2019-13
|View full text |Cite
|
Sign up to set email alerts
|

Takeaways from the Special Issue on The Practice of Replication

Abstract: In July 2017, Economics: The Open Access, Open Assessment E-Journal issued a call for papers for a special issue on "The Practice of Replication." In that call, the journal explained that there was no generally accepted procedure for how to do a replication. Likewise, there was no generally accepted standard for determining whether a replication "confirms or disconfirms" an original study. Accordingly, the journal called for papers to identify principles for how to do a replication and how to interpret its res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The CSI has had a huge impact. It seems to be a standard reference when discussing the (low) credibility of social science research with observational data (see e.g., Damian, Meuleman, and van Oorschot 2019; Reed 2019; Young 2018). Many, especially in media articles and Internet discussions, even concluded that the social sciences may not be rigorous enough: Findings depend to a large extent on who did the research.…”
Section: Introductionmentioning
confidence: 99%
“…The CSI has had a huge impact. It seems to be a standard reference when discussing the (low) credibility of social science research with observational data (see e.g., Damian, Meuleman, and van Oorschot 2019; Reed 2019; Young 2018). Many, especially in media articles and Internet discussions, even concluded that the social sciences may not be rigorous enough: Findings depend to a large extent on who did the research.…”
Section: Introductionmentioning
confidence: 99%
“…But we also use Frederick's CRT as a measurement device. Following Reed (2019), our study can thus be regarded as an "extension replication" that asks the question of whether the external validity of the Chandler et al study extends to populations other than the one they investigated.…”
Section: Introductionmentioning
confidence: 99%
“…; and (ii) Does the intensity of the diaspora impact differ by diasporas’ attributes? To answer the first research question, we conduct one of the six types of replication recommended by Reed (2017, 2019), namely: focus on the same subject population but use different data. Specifically, we examine whether the institutional development role of diasporas found in the earlier literature extends to modifications to the dataset, while targeting the same population of migrants in OECD host countries.…”
Section: Introductionmentioning
confidence: 99%